2020
DOI: 10.2139/ssrn.3687043
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Social Distancing: Theory and Empirical Evidence from Ontario during COVID-19

Abstract: We study the factors associated with compliance with social-distancing regulations using a unique dataset on the behaviour of Ontarians during the COVID-19 pandemic. To start, we build a simple theoretical model of social distancing in order to understand how some individual and community-level factors influence compliance. We test our model's predictions by designing and conducting a survey on Ontarians in which we elicit their degree of compliance with current distancing regulations as well as proposed regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
3
2
Order By: Relevance
“…Studies have found that those able to work from home or who had flexible work arrangements were better able to adhere to public health preventive measures (Brankston et al, 2020;Papageorge et al, 2021;Papanastasiou et al, 2020) while those living in apartments were less able to adhere (Papanastasiou et al, 2020). Consistent with these results, we found that parents who were essential workers and parents and children living in apartments were less able to adhere to public health preventive measures.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Studies have found that those able to work from home or who had flexible work arrangements were better able to adhere to public health preventive measures (Brankston et al, 2020;Papageorge et al, 2021;Papanastasiou et al, 2020) while those living in apartments were less able to adhere (Papanastasiou et al, 2020). Consistent with these results, we found that parents who were essential workers and parents and children living in apartments were less able to adhere to public health preventive measures.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, living in a household with 5 or more people predicted an increased likelihood of adherence in children, which could be due to the greater need to practice public health preventive measures in larger households to protect household members or less need to play or participate in activities outside the home. We did not find evidence that a family history of chronic disease predicted adherence, in contrast with Papanastasiou et al (2020) who found that chronic health conditions related to risk of complications from COVID-19 were associated with adherence to public health preventive measures (Papanastasiou et al, 2020). This could be due to our family history of chronic disease variable having been defined more broadly and to the younger age of our study participants.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…1 We are aware of no prior study recommend social-norm-based interventions to combat the COVID-19 pandemic, suggesting they are most effective when specific to an individual's social identity (Centola, 2011) or promoted by those central in a social network (Kim et al, 2015). Some studies measure respondent perceptions of social distancing norms (Papanastasiou et al, 2020;Xie et al, 2020;Arroyos-Calvera et al, 2021). Alsan et al (2020) find that correcting social norms about COVID-19 mask-wearing leads to more correct norm perceptions.…”
Section: Introductionmentioning
confidence: 99%